The new international studies classroom : active teaching, active learning - Lantis, Jeffrey S.; Kuzma, Lynn M.; Boehrer, John. (Boulder, Co. : Lynne Rienner Publishers, 2000)
This volume combines curricular themes and teaching methods to provide practical teaching tools for international studies faculty. The authors explore the case method, games, simulations, role-play exercises, and uses of technology. Each chapter features classroom activities.
Includes bibliographical references and index.
Keywords: International relations -- Study and teaching